KOMPOSISI FLORISTIK PADA BERBAGAI SUBTIPE GENANGAN DI HUTAN MANGROVE SUAKA MARGASATWA PULAU KAGET KECAMATAN TABUNGANEN KABUPATEN BARITO KUALA - Mahriannoor Akbar; Yusanto Nugroho; Gt. Syeransyah Rudi (Universitas Lambung Mangkurat, 2020)
Kaget Island, located in Tabunganen District, Barito Kuala Regency, is one of the mangrove areas located in the distal zone because this location includes locations far from the sea. Kaget Island Wildlife Reserve is one of the representatives of mangrove swamp forest ecosystem types. The purpose of this study was to analyze the index of importance in each inundation sub-type in the Kaget Island Wildlife Reserve Mangrove Forest and analyze the species diversity index and similarity index of various types of inundation sub-types obtained from important value indices in the region. The results obtained from this study that the important value index (INP) at each growth rate in the study location included in the criteria is low because there are few species found in all sub-types of inundation, especially at seedling and sapling, the highest INP at each growth rate found in the sub-type is always inundated. At the level of the lower plants are types of Cynum asiaticum L 66.51%, the level of seedlings is the type of Sonneratia caeseolaris 154.03%, the level of saplings is the type of Ficus annulata 200.00%, the level of pillars and trees is Sonneratia caeseolaris 256.09%. The level of diversity in the location of Kaget Island Mangrove Forest is classified as medium > 1 at the lower crop level, and at the level of the pole and tree classified as low ≤ 1. The similarity level in the shocked Mangrove Island Forest location is low because only the lower plants and pole and tree levels are has the same type, lower plant level has a high similarity value ≥ 80% and at the pole level and pophon has a medium similarity value ≤ 60%.Keywords: Mangrove; Important Value Index (INP); Diversity; Similarity